Transcriptome sequencing of Cocos nucifera leaves in response to Rhynchophorus ferrugineus infestation - Liu, Li; Yan, Wei; Liu, Bo (Frontiers in Genetics, 2023)
Red palm weevil (RPW, Rhynchophorus ferrugineus) is an invasive pest of palms. In China, coconut (Cocos nucifera) production is being significantly affected by the RPW attack. To develop a long-term RPW control strategy, host-plant resistance is the most sustainable option. In this regard, the availability of transcriptome sequencing data from RPW-infected coconut plants can be highly useful. Therefore, the present study assessed coconut leaf physiological responses and transcriptional changes after different days of RPW attack i.e., 5, 10, 15, 20, and 25 days after infestation (DAI). A comparison of physiological data indicated that populations with the higher number of RPW insects i.e., population C (15 males + 21 females) and D (20 males + 28 females) triggered higher antioxidant enzyme activities. We used this data to study the transcriptomic responses on 5 and 20 DAI. Of the 38,432 detected transcripts, 3984, 1981, 3925, and 2257 were differentially expressed in CK_vs_C (5DAI), CK_vs_D (5DAI), CK_vs_C (20 DAI), and CK_vs_D (20 DAI), respectively. These transcripts were enriched in plant-pathogen interaction, phenylpropanoid/flavonoid biosynthesis, amino sugar and nucleotide sugar metabolism, plant hormone signal transduction, mitogen-activated protein kinase, and reactive oxygen scavenging pathway. We discuss these results and present several candidate genes to be manipulated for developing a sustainable strategy to control RPW attack regarding host-plant resistance. Furthermore, these findings provide a basis for developing effective early and late RPW attack detection strategies.